The Polar Eskimo's eyes. - Gilberg, Lisbet; Gilberg, Aage (Meddelelser om Grønland, 1976)
In 1963 the authors carried out a four months' expedition to Thule District in North Greenland for the purpose of making an anthropological and genetic-biological study of our old friends, the Polar Eskimos, before urbanization grew out of hand. A total of 304 persons, or 95% of the highest possible number, from ten years of age and upwards were investigated. Blood samples were taken, and black and white photos of physiognomy, colour photos of eyes and faces, hand- and fingerprints, anthropometric measurements were made. Our pedigrees of the whole population were brought up to date, and were subsequently continued up to 1973. The eye-investigations in this paper are registered in regard to sex, age and descent. Quite commonly we found that females have darker eyes than males, and children have darker eyes than adults. 37 persons or 12,1% were found to have mixed coloured iris. Mongol fold, or similar folds, which pass through the margin of the lower eyelid were found in 209 persons or 68,75% Rima palpebralis was registered as round, with female predominance, elliptical, semielliptical and as a split, and in regard to direction quite horizontal, slanting a little upwards, with female predominance, and slanting downwards. Most Polar Eskimos have triangular eyebrows, right-angled upwards, and lateral. An appendix concerning the ear lobe form shows, that only 10% Polar Eskimos have real ( +) lobes, males three times as often as females.